Capital market financing, firm growth, and firm size distribution - Tatiana Didier; Ross Levine; Sergio L. Schmukler (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
How many and which firms issue equity and bonds in domestic and international markets, how do these firms grow relative to non-issuing firms, and how does firm performance vary along the firm size distribution (FSD)? To evaluate these questions, we construct a new dataset by matching data on firm-level capital raising activity with balance sheet data for 45,527 listed firms in 51 countries. Three main patterns emerge from the analysis. (1) Only a few large firms issue equity or bonds, and among them a small subset has raised a large proportion of the funds raised during the 1990s and 2000s. (2) Issuers grow faster than non-issuers in terms of assets, sales, and employment, i.e., firms do not simply use securities markets to adjust their financial accounts. (3) The FSD of issuers evolves differently from that of non-issuers, tightening among issuers and widening among non-issuers.
Keywords: F65; G00; G10; G31; G32; L25; 330; access to finance; bond markets; capital market development; capital raisings; firm dynamics; firm financing; stock markets